Técnicas de enseñanza en el funcionamiento del cuerpo de aceleración en los vehículos modernos y su influencia en el aprendizaje de los estudiantes de 3º. BGU del Colegio de Bachillerato José Peralta de la ciudad de Guayaquil - Ochoa León, Luis Polivio (2019)
With dollarization our country is backed by a strong currency in the world and that gave the opportunity to distributors to import a large number of automotive vehicles of different brands and models each year, such as: Chevrolet, Ford, Nissan, Renault, Kia, etc. As we know in our country there is a stage where technology borders all fields and even more in the area of automotive with the permanent innovations in each car. That is why the high school "José Peralta" of the City of Guayaquil, has the obligation to be updated with current technology in the automotive field where students will have the opportunity to learn a profession with a high degree of technical and scientific knowledge, that will allow them to have the opportunity to insert themselves in the labor world, or to continue their university studies. With the present work called, teaching techniques in the operation of the acceleration body in modern vehicles and its influence on the learning of 3rd grade students. BGU of the high school "José Peralta" of the City of Guayaquil, will aim to ensure that both teachers and students, have the necessary tools to develop skills in the handling and maintenance of the acceleration body of vehicles, plus We will reinforce the value of responsibility by creating awareness of work and compliance. This project is based on the problematic situation faced by the teacher at the time of teaching their technical classes in the area of automotive and will serve as an alternative when using strategies or methodological resources for the learning of third-year students in high school